Selection of Collagen Membranes for Bone Regeneration: A Literature Review - Sbricoli, Luca; Guazzo, Riccardo; Annunziata, Marco; Gobbato, Luca; Bressan, Eriberto; Nastri, Livia (Materials, 2020)
Several treatment modalities have been proposed to regenerate bone, including guided bone regeneration (GBR) where barrier membranes play an important role by isolating soft tissue and allowing bone to grow. Not all membranes biologically behave the same way, as they differ from their origin and structure, with reflections on their mechanical properties and on their clinical performance. Collagen membranes have been widely used in medicine and dentistry, because of their high biocompatibility and capability of promoting wound healing. Recently, collagen membranes have been applied in guided bone regeneration with comparable outcomes to non-resorbable membranes. Aim of this work is to provide a review on the main features, application, outcomes, and clinical employment of the different types of collagen membranes. Comparisons with non-resorbable membranes are clarified, characteristics of cross-linked collagen versus native collagen, use of different grafting materials and need for membrane fixation are explored in order to gain awareness of the indications and limits and to be able to choose the right membrane required by the clinical condition.